Deciphering the competence of microbial isolate in Synthetic consortium for dairy wastewater treatment (Funded Work) - ANUPAMA BHARDWAJ; JAGTAR SINGH; SONIA CHAMAN (International Journal of Pharma and Bio Sciences, 2017)
The present study was designed in two phases. In phase I,fourteen bacteria and six fungi were isolated from dairy effluent and their individual COD (Chemical Oxygen Demand) and BOD (Biological Oxygen Demand) removal efficiency was evaluated. Four microbial isolates E3, E5, E11 and F5 exhibiting more than 50% COD and BOD reduction were selected for formulation of synthetic consortium. On the basis of 16S and 5.8S rRNA sequencing these were identified as E3 (Serratia marcescens), E5 (Stenotrophomonas maltophilia), E11 (Brachybacetrium muris) and F5 (Cunninghamella echinulata). In phase II, four synthetic consortia were designed by incorporating the isolates in different proportion and combinations to treat three forms of dairy effluents .Consortium set D (5% Serratiamarcescens+ 5% Cunninghamella echinulata+ 3% Stenotrophomonas maltophilia + 3% Brachybacetrium muris)exhibited maximum level of removal of COD (89% ) and BOD (78%). This communication revealedthat exploitation of such efficient consortium (set D) can overcome the inefficiencies pre-existing with the biological wastewater treatment plants by acting as prospective candidate for bio-augmenting the native microflora.